Pengembangan Sistem Informasi Penjualan Awesam Merchandise Dengan Metode Rational Unified Process - Jebi Hayi Tamami; Yusi Tyroni Mursityo; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Economic growth in the information and communication sector in Indonesia continues to rise every year. This is driven by the number of internet users, for example online transactions. This positive growth has made changes spending patterns of Indonesian people increasingly shifting towards electronics or online shopping. Whereas Awesam sells products according to the wishes of the users still in the conventional way that makes customers have to come direclty to the store. The sales coverage is still small because it can only make sales in certain areas. The absence of customer-related database such as contacts, names and geographic information and purchase history makes a lack of service to customers. This certainly makes Awesam not able to compete in online sales. The solution to handle some of these problems is by developing a sales information system using Rational Unified Process (RUP) method based on Sales Force Automation (SFA). The final result of this research is a sales information system to assist the Awesam in handling each transaction, improve service to customers and face competition. Some tests carried out to maintain software quality including validation testing conducted to find out the functional system can run well which shows 100% valid, responsiveness testing to ensure the system can adapt to the size of the user's screen resolution shows that displays can adapt to 3 sizes of resolution properly. As well as compability testing to test non-functional requirements that indicate no errors have occurred.